Subdistrict-Level Reproductive Number for Foot and Mouth Disease in Cattle in Northern Thailand - Arjkumpa, Orapun; Picasso-Risso, Catalina; Perez, Andres; Punyapornwithaya, Veerasak (Frontiers in Veterinary Science, 2021)
Foot and mouth disease (FMD) is an important contagious transboundary disease that causes a significant economic loss for several countries. The FMD virus (FMDV) can spread very rapidly by direct and indirect transmission among susceptible animals. The complexity and magnitude of FMDV transmission at the initial stages of the epidemic can be expressed by the basic reproductive number (R0), and furthermore, control strategies can be assessed by the estimation of the effective reproductive number. In this study, we aimed to described FMD outbreaks among smallholder cattle farms by subdistricts in Thailand and compute the effective reproductive number for outbreaks caused by FMDV serotype O and overall serotypes at the subdistrict level (Rsd) using an epidemic doubling time method. Field data of FMD outbreaks during 2015-2017 that affected 94 subdistricts in northern Thailand were assessed to estimate the R_sd. Results showed that 63.38% (90/142) of the FMD outbreak episodes in cattle were caused by FMDV serotype O. The average doubling time and the (Rsd) estimated of the outbreaks caused by FMDV serotype O and overall serotype was 2.80 and 4.67 months, and 1.06 and 1.04, respectively. Our result indicated that FMD subdistrict transmission in cattle remains constant in northern Thailand within the three periods studied among each epidemic peak, which indicates the endemicity of the disease in the region. Although control measures are in place, our results highlighted the need for enhancing FMD monitoring and control strategies in northern Thailand.